Liver Histology During Mipomersen Therapy for Severe Hypercholesterolemia - Hashemi, Nikroo (J Clin Lipidol, 2014)
BACKGROUND: Mipomersen is an antisense oligonucleotide that inhibits apolipoprotein (apo) B synthesis and lowers plasma low density lipoprotein (LDL) cholesterol even in the absence of LDL receptor function, presumably due to the inhibition of hepatic production of triglyceride-rich very low density lipoprotein (VLDL) particles. By virtue of this mechanism, mipomersen therapy commonly results in the development of hepatic steatosis. Because this is frequently accompanied by alanine aminotransferase (ALT) elevations, concern has arisen that mipomersen could promote the development of steatohepatitis, which could in turn lead to fibrosis and cirrhosis over time. OBJECTIVE: The objective of this study was to assess the liver biopsy findings in patients treated with mipomersen. METHODS: We describe 7 patients who underwent liver biopsy during the mipomersen clinical development programs. Liver biopsies were reviewed by a single, blinded pathologist. RESULTS: The histopathological features were characterized by simple steatosis, without significant inflammation or fibrosis. CONCLUSION: These findings suggest that hepatic steatosis due to mipomersen is distinct from non-alcoholic steatohepatitis.